Thermal performance of a rectangular exhaust gas recirculation cooler subject to hydrocarbon and water vapor condensation - Razmavar, Ali Reza; Malayeri, M. Reza (International journal of thermal sciences, 2019)
The reliability of exhaust gas recirculation (EGR) coolers, which are commonly used to lower emission of nitrogen oxides (NOx) from diesel-driven engine cars, can profoundly be compromised by deposition of soot particles and hydrocarbon (HC) species on EGR surfaces. This study discerns the impacts of HC and water condensation on deposit formation of a rectangular EGR cooler with surrogate species of soot particles, water and icosane as heavy hydrocarbon. To do so, an experimental test facility was assembled in which a rectangular channel with removable plates was utilized to visualize deposition along with HC and water condensation. Icosane as a hydrocarbon which is common in diesel exhaust gases was injected to the exhaust gas stream during the experiments. The experimental results, under operating conditions attempted in this study, showed that HC condensation could be a dominant factor in diminishing particulate deposition if injected prior to the presence of soot particles, which is of practical implication. The change in coolant temperature from 90 °C to 25 °C also resulted in reduction of fouling resistance of up to 60%. It is thus preferable to maintain the coolant temperature as low as possible during the operation. Furthermore, the condensation of water vapor droplets on the cooler surface can partially result in deposit layer flake-off and consequently mitigate the EGR cooler fouling to some extent. •A novel in-situ technique to maintain thermal performance of EGR coolers.•Condensed icosane rolls over on the surface and may dislodge soot particles.•Coolant temperatures from 90 °C to 25 °C resulted in 60% decrease of Rf.•Water vapor in the exhaust gas improves the thermal performance of EGR coolers.